On relation between J-integral and heat energy dissipation at the crack tip in stainless steel specimens - Giovanni Meneghetti; Mauro Ricotta; Giuseppe Pitarresi (Fracture and Structural Integrity)
In this paper, an experimental procedure to evaluate the elastic-plastic J-integral at the tip of a fatigue crack is presented. According to this new approach, the elastic component of the J-integral is derived from Thermoelastic Stress Analysis, while the plastic component of the J-integral is derived from the heat energy loss. An analytical link is proposed to apply this new experimental technique. Therefore, the elastic-plastic J-integral range was evaluated starting from infrared temperature maps measured in situ during crack propagation tests of AISI 304L stainless steel specimens. It was found that the range of the infrared thermography-based J-integral correlated well the crack growth data generated in small as well as large scale yielding conditions. Finally, the experimental values of the J-integral were successfully compared with the corresponding numerical values obtained from elastic-plastic finite element analyses.